Pengaruh corporate social responsibility dan good corporate governance terhadap agresivitas perpajakan - Insani, Dea Anas Stasya; Wahyudin, Ahmad; Aini, Laily Nur; Anas, Zulviar (Nur Science Institute, 2022)
This study aims to empirically examine the effect of corporate social responsibility and GCG (good corporate governance) on tax aggressiveness. The dependent variable used in this study is aggressive tax planning, which is measured using ETR (effective tax rates). The independent variables in this study are corporate social responsibility and GCG (managerial ownership, audit committee, and audit quality). This study is based on a sample of 110 manufacturing companies listed on the Indonesia Stock Exchange in 2012–2016. The study sample was selected by purposive sampling and obtained from 22 companies per year that fulfill the criteria. Data were analyzed using multiple linear regression analysis. The results show that CSR, managerial ownership, and audit quality do not affect the action of aggressive tax. Meanwhile, the audit committee shows the existence of influence on the activity of aggressive tax.